Production of activated carbon from peat by chemical activation method / Noor Azlina Ibrahim - Ibrahim, Noor Azlina (2001)
Peat was used as the raw material to produce activated carbon by chemical activation method using phosphoric acid as activating agent. The activation was performed at the various activation temperatures, which were 500, 600 and 700 °C, and at different activation period (3 and 5 hour). Before that, the peat was impregnated first at various soaking time (4, 8 and 12 hour) with concentrated phosphoric acid in order to compare their effect on pore development in activated carbon. This research was carried out to study the effect of washing process before and after carbonization to the porosity of the chemically produced activated carbon. Iodine number determination and methylene blue decolorizing power were used to check the quality and porosity of activated carbon. This study showed that, washing sample after carbonization gave the higher iodine number and methylene blue value for the activated carbon produced. The optimum condition for the production of activated carbon from peat by chemical activation was at 500°C, 12 hours impregnation period and 5 hours activation period. These results showed that the impregnation is required in order to achieve large surface area of activated carbon.